2007
DOI: 10.1080/08839510701526954
|View full text |Cite
|
Sign up to set email alerts
|

Learning Drifting Negotiations

Abstract: International audienceIn this work, we propose the use of drift detection techniques for learning offer policies in multiissue, bilateral negotiation. Several works aiming to develop adaptive trading agents have been proposed. Such agents are capable of learning their competitors' utility values and functions, thereby obtaining better results in negotiation. However, the learning mechanisms generally used disregard possible changes in a competitor's offer/counter-offer policy. In that case, the agent's perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The aim is to analyze the agent's performance when an optimal or near-optimal policy has been discovered, and to observe the agent's capacity then to adapt itself to a modified environment. Enembreck et al (Enembreck et al, 2007) have shown that this is a good way to observe the behavior of an adaptive agent. We have analyzed the agent's adaptation with the k-NR and Q-Learning algorithms.…”
Section: K-nr Evaluationmentioning
confidence: 99%
“…The aim is to analyze the agent's performance when an optimal or near-optimal policy has been discovered, and to observe the agent's capacity then to adapt itself to a modified environment. Enembreck et al (Enembreck et al, 2007) have shown that this is a good way to observe the behavior of an adaptive agent. We have analyzed the agent's adaptation with the k-NR and Q-Learning algorithms.…”
Section: K-nr Evaluationmentioning
confidence: 99%
“…Figure 2 shows the architecture of an adaptive trade agent proposed in Ref. 4. Upon receiving an offer/counter-offer, the agent classifies it as interesting in case it has been accepted by the corresponding peer and non-interesting otherwise.…”
Section: Ensemble-based Drift Detection For Drifting Negotiationmentioning
confidence: 99%
“…In this section we use the offer definitions proposed in Ref. 4. Table 1 presents each of the issues used in this work.…”
Section: Offer Spacementioning
confidence: 99%
“…The goal is to analyze the agent's performance when an optimal or near-optimal policy was discovered and observe the agent's capacity to adapt itself again to environments with other features (see Figure 7). Enembreck et al [6] shown that this is a good way to observe the behavior of an adaptive agent. We have analyzed the agent's adaptation with the Q ε -learning and Q-PR-BAP algorithms.…”
Section: A Performance Of the Agent With Q-pr-bapmentioning
confidence: 99%